2003
DOI: 10.1007/s00428-004-1024-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage in placentas from normal and pre-eclamptic pregnancies

Abstract: Placental oxidative stress was suggested to play a role in the pathogenesis of pre-eclampsia (PE). In this study, levels of 8-hydroxy-2'-deoxyguanosine (8-OH-dG), a well-established marker of oxidative DNA damage, were analysed in placental cellular DNA from normal (group NP) and pre-eclamptic (group PE) pregnancies as well as from PE pregnancies complicated by intrauterine growth restriction (group PE-IUGR). Placental samples obtained immediately after delivery were frozen at -80 degrees C until analysis. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Other studies on the same subject showed similar conclusions, with oxidative stress levels being higher in the groups that exhibit both pathologies (Fujimaki et al 2011;Mert et al 2012). These findings suggest a correlation be-tween the severity of the deficiency in the interaction between cytotrophoblasts and the maternal spiral arteries, both representative of IUGR and PE, and the levels of oxidative stress (Wiktor et al 2004).…”
Section: Intrauterine Growth Restrictionsupporting
confidence: 69%
See 2 more Smart Citations
“…Other studies on the same subject showed similar conclusions, with oxidative stress levels being higher in the groups that exhibit both pathologies (Fujimaki et al 2011;Mert et al 2012). These findings suggest a correlation be-tween the severity of the deficiency in the interaction between cytotrophoblasts and the maternal spiral arteries, both representative of IUGR and PE, and the levels of oxidative stress (Wiktor et al 2004).…”
Section: Intrauterine Growth Restrictionsupporting
confidence: 69%
“…The PE plus IUGR group presented the highest 8-OHdG levels, with a significant difference from control. The PE group, however, showed no statistically significant difference from control (Wiktor et al 2004). Other studies on the same subject showed similar conclusions, with oxidative stress levels being higher in the groups that exhibit both pathologies (Fujimaki et al 2011;Mert et al 2012).…”
Section: Intrauterine Growth Restrictionmentioning
confidence: 69%
See 1 more Smart Citation
“…Type 1 diabetes offers a very hostile intrauterine environment, and is associated with high rates of fetal morbidity, including increased risks of congenital malformation, spontaneous abortion and perinatal death [39]. The fetal morbidity associated with maternal diabetes (and other embryopathies) reflects increased intrauterine oxidative stress and fetal oxidative DNA damage [11,12,[17][18][19][20][21][22][23][24]. The increased fetal DNA damage described in diabetes pregnancy must lead to increased telomeric DNA damage, as the GGG sequence in telomeric DNA is particularly susceptible to DNA damage [17].…”
Section: Discussionmentioning
confidence: 99%
“…Rates of telomere shortening at cell division are highly dependent on oxidatively induced strand breaks in telomeric DNA and oxidative DNA damage [11,12,17,18]. Feto-placental telomere attrition is an attractive hypothetical bridge between the adverse intrauterine environment and preprogramming of the offspring towards senescent phenotypes [19][20][21], as an adverse intrauterine environment increases oxidative damage to feto-placental DNA and fetal vascular endothelium [22][23][24]. We have previously suggested that this mechanism could account for a senescent phenotype in the adult offspring of women with type 1 diabetes [25].…”
Section: Introductionmentioning
confidence: 99%